Challenges in HIV/AIDS prevention, care and treatment programme in India (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2010)
This paper explores the pertinent challenges of Government’s HIV/AIDS prevention, care and treatment program in India. Study is mainly based on observations made during field visits, discussion during review meetings at various levels and during training programmes of various functionaries from April 2007-November 2009. The paper also takes into account the observations made on the conclusion of the Mid-term Review conducted by the Government of India in during July- December 2009 after completion of first 2.5 years of the 5-year plan of NACP-III. Additionally, interactions with key program managers involved in implementation and management of HIV/AIDS Program at the state, district and facility levels. Though numerous efforts have been made and continued by the Government and partners, HIV prevention, care and treatment services have not been able to reach to the most-at-risk population, specifically in the rural population. Socio-cultural and managerial issues are the key challenges reported by the most of the key implementers. There is an urgent need to address and strengthen the whole spectrum of health systems through a collaborative approach to achieve the millennium development goals of universal access to prevention, care and treatment services in India. DOI: 10.3126/saarctb.v7i1.3955SAARC J. TUBER. LUNG DIS. HIV/AIDS 2010 VII(1) 1-7